The Effect of Financial Literacy, Lifestyle, and Financial Attitudes on Financial Management Behavior of SPayLater Users in Management Study Program Students of the 22nd Batch in Yogyakarta City - Angela Febriani Saputri; Rinaldi Rinaldi (Universitas KH. Abdul Chalim Mojokerto, 2026)
The development of digital financial technology has encouraged the increasing use of Buy Now Pay Later (BNPL) services such as SPayLater among students. The ease of this transaction can trigger the risk of consumptive behavior if it is not balanced with good financial management skills. This study aims to analyze the influence of financial literacy, lifestyle, and financial attitudes on the financial management behavior of SPayLater users in the 2022 batch of Management Study Program students in Yogyakarta City. The research method used was quantitative with a causal associative design and a cross-sectional approach. The research sample amounted to 50 respondents who were selected using purposive sampling techniques. Data collection was carried out using a Likert scale questionnaire and analyzed through multiple linear regression using the help of statistical software. The results of the study showed that financial literacy and lifestyle had a significant but negative effect on financial management behavior, while financial attitudes had a significant positive effect. Simultaneously, the three variables had a significant effect on financial management behavior with a determination coefficient value of 83.7%. These findings confirm the importance of forming a good financial attitude so that students are able to manage the use of paylater wisely and responsibly.